Entrepreneurship, entry and performance of new business compared in two growth regimes: East and West Germany - Michael Fritsch (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2004)
The paper provides an outline of the concept of regional growth regimes and empirically illustrates the relevance of the concept. The empirical examples are entrepreneurship, entry and the performance of new businesses in East and West Germany. The differences of the factors determining the formation of new businesses as well as their development between these two growth regimes are immense and clearly demonstrate the relevance of region specific factors. – – Der Aufsatz skizziert das Konzept regionaler Wachstumsregime und illustriert die Relevanz des Konzepts mit einem empirischen Beispiel. Als Beispiel dienen Entrepreneurship, Marktzutritt und Erfolg von neu gegründeten Betrieben in Ost- und Westdeutschland. Die Unterschiede hinsichtlich der Bestimmungsgründe von Gründungen als auch die Unterschiede ihrer Entwicklung sind immens und belegen klar die Relevanz von regionalspezifischen Faktoren.
Keywords: O11; O18; P25; R11; 330; Growth regimes; new business formation; new business performance; location; regional influences; Wachstumsregime; Betriebsgründungen; Gründungserfolg; Standort; regionale Einflüsse; Entrepreneurship-Ansatz; Unternehmensgründung; Markteintritt; Erfolgsfaktor; Standortfaktor; Region; Alte Bundesländer; Neue Bundesländer; Deutschland